Konsep dan Strategi Upaya Pelestarian Kerajinan Laker Palembang Melalui Pelatihan dan Workshop - husni mubarat; Safar Junoko (Besaung : Jurnal Seni Desain dan Budaya, 2021)
This research is focused on aspects of the Process and Identification of Lkauer Crafts in Palembang, with the objectives being, 1) to support efforts to preserve the art of laker crafts in Palembang, 2) to find out the development of the design of the laker craft, 3) to find out the local cultural values contained in Palembang laker crafts, 4) to add insight and teaching materials to art and design lectures, especially DKV. The method used is descriptive qualitative method, with the method of collecting field observation data, which is to see firsthand the laker handicraft products in the craft center, and at the Bala Putra Dewa Museum in Palembang, the data collection method is also carried out by interviewing techniques and documenting the object research. The results of the data processing are the authors' analysis through the identification of problems encountered in the field. From these results the conclusions drawn by the author are summarized in the form of a draft strategy for the preservation of the laker craft. In addition to preservation efforts, the laker craft can also provide business opportunities and employment opportunities for the people of Palembang city, of course it cannot be separated from the assistance of the Regional Government in the form of training, workshops, capital assistance as well as providing a place for marketing.